PEMANFAATAN TEPUNG KACANG HIJAU (Vigna radiata) SEBAGAI SUMBER PROTEIN PADA PEMBUATAN OPAK KETAN KHAS TASIKMALAYA, JAWA BARAT - Mirna Isyanti Isyanti (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract Sticky rice opak is a processed food product made from glutinous rice with a crunchy and savory texture, round and flat in shape, through drying and roasting processes, until it is slightly brown in color. Sticky rice opak industry is spread across West Java, one of which is Tasikmalaya. Research on the manufacture of sticky rice opak products has been carried out by utilizing mung bean flour as a source of vegetable protein. The addition of mung bean flour in the manufacture of sticky rice opak aims to increase the nutritional value of the product. Results based on the organoleptic assessment, the panelists preferred the sticky rice opak product with the addition of 10% mung bean flour. The addition of mung bean flour up to 40% is still acceptable from the parameters of taste, aroma, texture, and color. Proximate analysis of the sticky rice opak preferred by the panelists (10% mung bean flour) showed a moisture content value of 4.06% and the original glutinous opak product (100% glutinous rice) of 4.14%. The protein content of sticky rice opak with the addition of mung bean flour showed a greater content (11.0%) than the original glutinous opak (8.16%). The addition of mung bean flour to sticky rice opak showed a slightly higher fatcontent and ash content than the original sticky rice opak. The original sticky rice opak made from 100% glutinous rice shows a higher carbohydrate content. Utilization of mung bean flour can be used to increase the protein content of sticky rice opak and can be an alternative innovation in the development of Tasikmalaya sticky rice opak products.Abstrak Opak ketan merupakan produk pangan olahan berbahan dasar beras ketan dengan tekstur yang renyah dan gurih, berbentuk bulat dan pipih, melalui proses penjemuran, dan pemanggangan, hingga warnanya agak kecoklatan. Industri opak ketan tersebar di daerah Jawa Barat, salah satunya adalah Tasikmalaya. Penelitian pembuatan produk opak ketan telah dilakukan dengan memanfaatkan tepung kacang hijau sebagai salah satu sumber protein nabati. Penambahan tepung kacang hijau dalam pembuatan opak ketan bertujuan untuk meningkatkan nilai gizi produk. Berdasarkan hasil penilaian organoleptik, produk opak ketan yang disukai panelis adalah dengan penambahan 10% tepung kacang hijau. Penambahan tepung kacang hijau sampai dengan 40% masih dapat diterima dari parameter rasa, aroma, tekstur, dan warna. Analisis proksimat produk opak ketan yang disukai oleh panelis (10% tepung kacang hijau) menunjukkan nilai kadar air sebesar 4,06% dan opak ketan original (100% beras ketan) sebesar 4,14%. Kadar protein opak ketan dengan penambahan tepung kacang hijau menunjukkan kandungan yang lebih besar (11,0%) dibandingkan opak ketan original (8,16%). Penambahan tepung kacang hijau pada opak ketan menunjukkan kadar lemak dan kadar abu sedikit lebih tinggi dibandingkan opak ketan original. Opak ketan original terbuat dari 100% beras ketan menunjukkan kandungan karbohidrat yang lebih tinggi. Pemanfaatan tepung kacang hijau dapat digunakan untuk meningkatkan kandungan protein opak ketan dan dapat menjadi alternatif inovasi dalam pengembangan produk opak ketan khas Tasikmalaya.